Given that lim x-> f(x)=6 and that lim x-> g(x)= -4, evaluate the following limit. Assume that c is a constant.
lim -2f(x) - 12 / g(x).
x->. I did
-2(6) - (12/-4)
-12 - (-3)
-12 + 3 = -9
Given that lim x-> f(x)=6 and that lim x-> g(x)= -4, evaluate the following limit. Assume that c is a constant.
lim -2f(x) - 12 / g(x).
x->. I did
-2(6) - (12/-4)
-12 - (-3)
-12 + 3 = -9
Looks good.
You may want to say: "By linearity of limits," or something of this nature. Although, this is pre-cal so it doesn't matter.....